The Consequences of a Large Number of Light Truck Vehicle (International Journal of Innovative Research in Engineering & Management, 2021)
Aerodynamics is dominated by the outer design of the vehicle  and extra internal components, such as the deflector connected.  It is widely known that in the Indian Subcontinent a large  number of light trucks without any aerodynamic characteristics  are produced and operated. The main purpose of this study is  therefore to assess the effect of aerodynamic devices or railways  on light-duty vehicles in Pakistan and Bangladesh. The research  consisted of computer modelling, production of quick physical  models and wind tunnel testing, as well as CFD analysis.  Nevertheless, there are a dangerous number of light trucks in the  Indian sub-continent, mostly in India, Bangladesh and Pakistan  that operate by changing an arrangement truck for Bedford J.  The drag forces of each model were examined and matched. The  results indicate that aerodynamically competent deflectors may  increase the aerodynamic drag by up to 22% for most locally  produced Pakistani and Bangladeshi vehicles. The aerodynamic  fitting may reduce fuel consumption by 12% by altering the  deflectors.
Keywords: Aerodynamic; Deflectors; Drag Coefficient; Drag Force; Light Truck